Produksi Biomassa dan Bahan Bioaktif Kolesom (Talinum triangulare (Jacq.) Willd) dari Berbagai Asal Bibit dan Dosis Pupuk Kandang Ayam - Hilda Susanti; Sandra Arifin Aziz; Maya Melati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
Field experiment to study biomass and bioactive compound productions of   Talinum triangulare from different propagules and chicken manure dosages was conducted at Leuwikopo, Dramaga, Bogor, West Java, Indonesia from September to November 2005.  The research used split plot design with 3 replications.  The main plot was propagules (seed and stem cutting) and sub plot was chicken manure dosages (0, 5, 10, and 15 t ha-1). Bioactive compound was determined qualitatively. The results showed that stem cutting gave the highest leaf dry weight (7.78 g plant-1) and tuber dry weight (4.99 g plant-1). The bioactive compounds (alkaloid, steroid, saponin, tannin, and flavonoid) were not influenced by propagules. The dosage of 15 t ha-1 chicken manure gave the highest leaf dry weight (10.73 g plant-1) and tuber dry weight (6.36 g plant-1). The bioactive compound decreased with the increasing chicken manure dosages. Interaction of stem cutting and 15 t ha-1 of chicken manure gave the highest leaf dry weight (12.43 g plant-1).   Bioactive compound and tuber dry weight were not influenced by the interaction of  propagules and chicken manure dosages.   Key words:  Bioactive compound, Talinum triangulare, propagules, chicken manure